Continuing Medical Education via Telemedicine and Sustainable Improvements to Health - Fuhmei Wang (International Journal of Telemedicine and Applications)
Background. This research aims to investigate the quantitative relationship between telemedicine and online continuing medical education (CME) and to find the optimal CME lectures to be delivered via telemedicine to improve the population’s health status. Objective. This study examines the following: (1) What factors foster learning processes in CME via telemedicine? (2) What is the possible role of online CME in health improvement? And (3) How optimal learning processes can be integrated with various health services? Methods. By applying telemedicine experiences in Taiwan over the period 1995–2004, this study uses panel data and the method of ordinary least squares to embed an adequate set of phenomena affecting the provision of online CME lectures versus health status. Results. Analytical results find that a nonlinear online CME-health nexus exists. Increases in the provision of online CME lectures are associated with health improvements. However, after the optimum has been reached, greater provision of online CME lectures may be associated with decreasing population health. Conclusion. Health attainment could be partially viewed as being determined by the achievement of the appropriately providing online CME lectures. This study has evaluated the population’s health outcomes and responded to the currently inadequate provision of online CME lectures via telemedicine.